Analysis of Digital Banking Product Marketing Strategies in Enhancing Business Performance (Case Study at Bank BJB) - Ahmad Erawan; Tongam Sirait (Al-Makki Publisher, 2024)
This study investigates the marketing strategies of digital banking products at Bank BJB, aiming to enhance business performance amid increasing competition in Indonesia's banking sector. The introduction outlines the significant transformation in the banking industry due to the rise of digital banking and fintech, emphasizing the necessity for banks to innovate to attract tech-savvy customers, particularly millennials and Generation Z. The research method employed a qualitative approach, utilizing in-depth interviews and document analysis to assess the effectiveness of Bank BJB's marketing strategies, particularly through its BJB Digi application. Results indicate that while Bank BJB has leveraged regional partnerships and diversified its digital services, it faces challenges such as suboptimal user experience and limited market penetration outside its core areas. The discussion highlights the need for improved marketing strategies to enhance customer engagement and business performance. In conclusion, the study recommends that Bank BJB focus on technological innovation, strategic collaborations, and aggressive marketing efforts to strengthen its competitive position in the digital banking landscape, thereby optimizing its service offerings andexpanding its customer base